Analysis of MSK jamming effectiveness based on effective jamming coefficient - Zengmao CHEN; Qian YAN; Zhiguo SUN; Rongchen SUN (Tongxin xuebao)
For the problem of communication jamming effectiveness, an effective jamming coefficient was proposed as an evaluation metric based on the correlation between jamming and communication signals, and the impact of orthogonal receivers was analyzed.Specially, minimum shift keying (MSK) and several typical binary modulation signals were chosen as the target communication and jamming signals, respectively.Jamming effectiveness evaluation was performed for the above mentioned scenario by deriving its theoretical bit error rate (BER) formulas.Moreover, for coherent jamming scenario with MSK being the jamming signal, the impact of its phase difference, frequency difference and delay on the jamming effectiveness were also systematically analyzed.The analysis suggests that to achieve better jamming effectiveness, different jamming modulation scheme should be chosen according to the signal-to-noise (SNR) of the jamming communication signal.Simulation has also shown that there is a good match between the derived theoretical analysis and numerical simulation of the proposed method effectiveness, which has proven its accuracy and validity.